Grãos secos de destilaria com solúveis em dietas para tilápia-do-Nilo - Botelho, Renan de Mattos [UNESP] (2015)
This study aimed to determine the nutritional value of corn distillery dry grain with soluble (CDDGS) produced in Brazil, as well as replacement of soybean meal protein (SM) by the CDDGS in diets for Nile tilapia. Was conducted study to evaluate the apparent digestibility coefficients (ADC) of nutrients and energy from the SM and CDDGS. ADC were determined by the indirect method (0.1% Cr2O3 as an inert indicator) based on replacement of 30% of a reference diet (26.81 DP and 3036 kcal kg- 1 DE) by test ingredients (SM and CDDGS). For the growth performance, 220 juveniles (mean weight of 32.89 ± 1.05 g) were distributed in 20 tanks (250 L). The fish were fed isocaloric and isoproteic diets containing replacement levels of 10, 30, 50 and 70% of SM protein by protein CDDGS and a control diet without replacement, formulated based on digestible values obtained in the digestibility study for the SM and CDDGS. At the end of 90 days were evaluated the performance parameters and feed utilization, intestinal morphology and determination of hematological profile. After this period, 10 fish per treatment were subjected to grading-induced stress and hematological profile was determined. Growth performance and feed utilization were not affected by treatments, as well as hematological parameters before and also after grading-induced stress, however there was a increase (P˂0.05) for villus:crypt ratio in fish fed diets containing replacement of 50 and 70% of SM protein by protein CDDGS. An increase (P˂0.05) in hematocrit and hemoglobin fish fed diet with replacement of 30% and total plasmatic protein and albumin in receiving diet with 50% replacement. It was observed leucopenia, lymphopenia and neutrophilia increase in plasma glucose concentrations for all fish after stress. The protein CDDGS can replace the SM protein up to 70% without impair growth performance and health, and improve the integrity of the ...